Position statement of the European Academy of Dermatology and Venereology Task Force on Quality of Life and Patient Oriented Outcomes on quality of life issues in dermatologic patients during the COVID‐19 pandemic. (29th June 2020) - Chernyshov, P.V.; Tomas‐Aragones, L.; Augustin, M.; Svensson, A.; Bewley, A.; Poot, F.; Szepietowski, J.C.; Marron, S.E.; Manolache, L.; Pustisek, N.; Suru, A.; Salavastru, C.M.; et al.
Abstract: The pandemic of COVID‐19 is a global challenge for health care, and dermatologists are not standing apart from trying to meet this challenge. The European Academy of Dermatology and Venereology (EADV) has collected recommendations from its Task Forces (TFs) related to COVID‐19. The Journal of the EADV has established a COVID‐19 Special Forum giving free access to related articles. The psychosocial effects of the pandemic, an increase in contact dermatitis and several other skin diseases because of stress, disinfectants and protective equipment use, especially in healthcare workers, the temporary limited access to dermatologic care, the dilemma whether or not to pause immunosuppressive therapy, and, finally, the occurrence of skin lesions in patients infected by COVID‐19 all contribute to significant quality of life (QoL) impairment. Here, we present detailed recommendations of the EADV TF on QoL and patient‐oriented outcomes on how to improve QoL in dermatologic patients during the COVID‐19 pandemic for several different groups of patients and for the general population.